(untitled) (Al-Aasar, 2025)
This research critically examines the stylistic dimensions of al-Tarjamah al-Fiqhiyyah (jurisprudential chapter headings) in Sahih al-Bukhari, focusing on rhetorical and literary features such as saj‘ (rhymed prose), tibaq (antithesis), jinās (paronomasia), and overall balāghah (eloquence). Imam al-Bukhari, through his chapter headings, not only introduced legal concepts but also embedded linguistic artistry that reflects the precision and sophistication of classical Arabic expression. This study explores how these rhetorical devices enhance the textual coherence, semantic depth, and jurisprudential inference of the tarājim, offering an intertextual blend of legal thought and literary finesse. Drawing on classical Arabic rhetorical theories and traditional commentaries, the analysis reveals that Imam al-Bukhari’s stylistic choices were deliberate and served both didactic and aesthetic functions. This paper aims to contribute to a deeper understanding of the literary elements embedded in hadith sciences and shed light on an often-overlooked dimension of Sahih al-Bukhari